Thermophile 90S pre-ribosome structures reveal the reverse order of co-transcriptional 18S rRNA subdomain integration - Cheng, Jingdong; Baßler, Jochen; Fischer, Paulina; Lau, Benjamin; Kellner, Nikola; Kunze, Ruth; Griesel, Sabine; Kallas, Martina; Hurt, Ed (Molecular cell, 2019)
Eukaryotic ribosome biogenesis involves RNA folding and processing that depend on assembly factors and small nucleolar RNAs (snoRNAs). The 90S (SSU-processome) is the earliest pre-ribosome structurally analyzed, which was suggested to assemble stepwise along the growing pre-rRNA from 5′ > 3′, but this directionality may not be accurate. Here, by analyzing the structure of a series of 90S assembly intermediates from Chaetomium thermophilum, we discover a reverse order of 18S rRNA subdomain incorporation. Large parts of the 18S rRNA 3′ and central domains assemble first into the 90S before the 5′ domain is integrated. This final incorporation depends on a contact between a heterotrimer Enp2-Bfr2-Lcp5 recruited to the flexible 5′ domain and Kre33, which reconstitutes the Kre33-Enp-Brf2-Lcp5 module on the compacted 90S. Keeping the 5′ domain temporarily segregated from the 90S scaffold could provide extra time to complete the multifaceted 5′ domain folding, which depends on a distinct set of snoRNAs and processing factors.
Gesehen am 18.10.2019